Risky business [videorecording (DVD)] - Brickman, Paul; Cruise, Tom, 1962-; DeMornay, Rebecca, 1963-; Pantoliano, Joe; Masur, Richard; Pinchot, Bronson; Pryor, Richard, 1940-2005 (Warner Home Video, 2008)
Joel's wealthy suburban Chicago parents are going on vacation and leaving him in charge of the house. They trust their college-bound 17-year-old son but they shouldn't. Every kid's dream is every parent's nightmare. No sooner do Joel's parents step on the plane than he raids the liquor cabinet, has a joyride in Dad's Porsche, and has a night of passion with a young call girl named Lana.